2016
DOI: 10.18632/oncotarget.9981
|View full text |Cite
|
Sign up to set email alerts
|

MiR-495 inhibits esophageal squamous cell carcinoma progression by targeting Akt1

Abstract: MicroRNAs are involved in tumor initiation and progression by regulating oncogenes and tumor suppressor genes. Here we found that miR-495 are lower in clinical ESCC tissues than in adjacent non-tumor tissues. Moreover, the lower miR-495 expression correlated with increased lymph node metastasis (LNM), invasion and TNM stage. miR-495 overexpression predicted a favorable outcome in ESCC patients. miR-495 targeted a site in the 3′-UTR of Akt1, and miR-495 levels correlated inversely with Akt1 protein levels in ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Partly in line with our study, Dou et al have also clarified that upregulated PKIB can activate the PI3K/AKT signaling pathway in non‐small cell lung cancer . Although a recent study reported that miR‐495 could target AKT in 293 cells by dual‐luciferase report assay, our study only confirmed that miR‐495 might affect the expression of p‐AKT by targeting PKIB, but did not affect total AKT, thus inhibiting the PI3K/AKT signaling pathway. Similar results were found in a previous study that miR‐495 directly targets IGF1, and regulates AKT pathway activity in oral tumors through miR‐495/IGF1 axis .…”
Section: Discussionsupporting
confidence: 90%
“…Partly in line with our study, Dou et al have also clarified that upregulated PKIB can activate the PI3K/AKT signaling pathway in non‐small cell lung cancer . Although a recent study reported that miR‐495 could target AKT in 293 cells by dual‐luciferase report assay, our study only confirmed that miR‐495 might affect the expression of p‐AKT by targeting PKIB, but did not affect total AKT, thus inhibiting the PI3K/AKT signaling pathway. Similar results were found in a previous study that miR‐495 directly targets IGF1, and regulates AKT pathway activity in oral tumors through miR‐495/IGF1 axis .…”
Section: Discussionsupporting
confidence: 90%
“…However, there are different views on the role of miR-495 in regulating tumor invasion and migration. It has been reported that miR-495 suppresses the aggressive behaviors of glioma [11], prostate cancer [12] and esophageal squamous cell carcinoma cells [13]. However, in breast [14], bladder [15] and gastric [16] cancer cells, this miRNA promotes tumor invasion and migration.…”
Section: Introductionmentioning
confidence: 98%
“…Downregulation of miR-495 is frequently observed in various types of human cancer (21)(22)(23)(24). For example, miR-495 is downregulated in medulloblastoma tissues and cell lines; patients with medulloblastoma and decreased expression levels of miR-495 exhibit poorer prognosis compared with those expressing higher miR-495 levels (21).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-495 has been reported as an independent predictor of overall survival in patients with medulloblastoma (21). In esophageal squamous cell carcinoma, the expression levels of miR-495 were reported to be reduced in tumor tissues and significantly associated with lymph node metastasis, invasion and tumor, node and metastasis (TNM) stage (22). miR-495 was observed to be expressed at low levels in glioma (23,24), osteosarcoma (25), colorectal (35,36), gastric (37-39), prostate (40) and endometrial cancers (41), and renal cell carcinoma (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation